The Role of Tax Consultants in Handling the SP2DK Case Owned by Taxpayer A - Intan Oktavia; Asaprima Putra Karunia; Mauliza Amigia; Fahmi Setiadi; Meka Sabilla Salim (FISCAL: Jurnal Akuntansi dan Perpajakan, 2026)
This study aims to investigate the role of PT X as a tax consultant in handling the case of a Request for Explanation of Data and/or Information (SP2DK) received by individual taxpayer A (WP A) for the first time. This study investigated the cause of Taxpayer A receiving SP2DK for the first time, the final decision made by Taxpayer A in resolving the case, and the role of PT X as a tax consultant who assisted Taxpayer A. The research method used is descriptive, involving brief interviews with the tax consultant and data collection as supporting data. The finding in this case underscores the potential benefits of professional assistance for taxpayers lacking a tax accounting background, as it can prevent errors in revenue recapitulation and underpayment of Final Income Tax as per Government Regulation number 23/46. This study aims to provide recommendations on the need for tax consultant services, thereby enhancing their understanding of taxation.